Prediction of Lactation Milk Yield from Part Yield in Jaffarabadi Buffalo - Chaudhari, Pravin N.; Gadariya, Mahesh R.; Kapadiya, Pratik S.; Gamit, Pranav M.; Savaliya, Bhagavanji D. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
An attempt was made to predict standard lactation milk yield (SLMY) by simple regression equation from weekly, fortnightly and monthly, individual and cumulative part yield in Jaffarabadi buffalo. A total of 176 normal lactations of Jaffarabadi buffaloes from 1st to 6th parity with lactation length >210 days were analysed. Correlation coefficients between 305-days milk yield (SLMY) and different weekly (1st to 20th week), fortnightly (1st to 5th fortnight) and monthly (1st to 5th month), individual and cumulative part lactations were positive and significant (P <0.01) and showed increasing trend with advancement of lactation. The reliability of prediction for SLMY was reasonably high, i.e., 63 to 67% for 18th or 19th week, 67 to 68% with 9th or 10th fortnight, and 63 to 67% for 4th or 5th month part lactation yields when used as independent variables. From 20th week, the correlation and accuracy of regression for SLMY reduced. Individual part yields were found to be more reliable than cumulative respective (weekly, fortnightly and monthly) part yields for prediction of SLMY. First 100-days milk yield as part lactation covered only 49% of variation in SLMY in Jaffarabadi buffaloes, which implies that one must be cautious while sire evaluation based on first 100-d yield as part lactation of daughters under progeny testing programmes or determining production potential in terms of LMY based on part lactation of Jaffarabadi buffaloes.